Working Life Quality among Clinical Nurses in Intensive Care Unit: A Phenomenology Study - Sofiana; Adi Pamungkas, Rian; Dian Purwati, Wahyuni (International Journal of Nursing and Health Services (IJNHS), 2022)
Background. The quality of a nurse's work life is a nurse's perception or assessment of all dimensions that affect the quality of her work related to her experience in working in order to achieve organizational goals. The quality of work life of clinical nurses has an important role in health services in hospitals. Method: The research design in this study is qualitative research with a phenomenological approach. This qualitative study aims to explore the quality of work life of clinical nurses in Intensive Care Unit. We conducted in-depth interviews with ten key nurse informants who work in intensive care units such as the Emergency Room, Intensive Care Unit, Operating Room, Hemodialysis Unit, and Perina Room, which were selected based on purposive sampling. Interviews were recorded and transcribed verbatim. Results: The research results in this qualitative study, that affect the quality of work life of clinical nurses in intensive care unit consist of: 1) fluctuating workload; 2) additional duties of nurses; 3) inappropriate reward system; 4) career development and recognition of work performance; 5) nurses' work stress level. Conclusion: Our findings provide valuable information for hospital management to pay attention to clinical nurses working in intensive care unit in improving the quality of their work life